Monitoring of oil spills using airborne and spaceborne sensors - Singh K.P. (My University, 2025)
The importance of airborne and spaceborne radars in the detection, surveillance and corrective measures for oil pollution is well established. With the advent of modern technology, increased offshore oil and gas exploration, and production in areas with moderate and extreme weather conditions have increased the possibility of serious environmental damage due to oil-spills. Extended and improved surveillance using air/spaceborne Scatterometer, radiometer, SLAR, and SAR can reduce potential damage alongwith improved and efficient of clean up operation. This kind of effort may potentially reduce the hazards to homo-sapiens by deliberate or even unintentional pollution. © 1995.